Quantifying individual noxious-evoked baseline sensitivity to optimise analgesic trials in neonates - Cobo, MM; Hartley, C; Gursul, D; Andritsou, F; van der Vaart, M; Schmidt Mellado, G; Baxter, L; Duff, EP; Buckle, M; Evans Fry, R; Green, G; Hoskin, A; et al. (eLife Sciences Publications, 2021)
Despite the high burden of pain experienced by hospitalised neonates, there are few analgesics with proven efficacy. Testing analgesics in neonates is experimentally and ethically challenging and minimising the number of neonates required to demonstrate efficacy is essential. EEG (electroencephalography)-derived measures of noxious-evoked brain activity can be used to assess analgesic efficacy; however, as variability exists in neonate’s responses to painful procedures, large sample sizes are often required. Here, we present an experimental paradigm to account for individual differences in noxious-evoked baseline sensitivity which can be used to improve the design of analgesic trials in neonates. The paradigm is developed and tested across four observational studies using clinical, experimental, and simulated data (92 neonates). We provide evidence of the efficacy of gentle brushing and paracetamol, substantiating the need for randomised controlled trials of these interventions. This work provides an important step towards safe, cost-effective clinical trials of analgesics in neonates.